Needs Analysis for Developing Environmental Care Attitudes for students of Social Studies Education Program - Af’aliyah, Khoirotul; Cholifah, Nur; Sasi, Wahyuning; Saputri, Afif Berlian (Proceeding of International Conference on Islamic Education (ICIED); Vol 9 No 1 (2024): Proceeding of International Conference on Islamic Education (ICIED)DO - 10.18860/icied.v9i1.3175, 2024)
Environmental sustainability is an important issue and should be a concern in every field, especially education. The attitude of caring for the environment is one of the characteristics that must be developed starting from the realm of elementary school to college. However, there are still many students who seem indifferent to environmental cleanliness. This research is a quantitative descriptive study with the aim of knowing the need for the development of environmental care attitudes through a survey of the level of attitude towards cleanliness, energy saving, and the application of the 3Rs of Social Science Education study program students. The results showed that there are still many Social Studies Education Study Program students who do not care about environmental cleanliness such as throwing garbage out of place in the classroom area, not turning off the electricity after finishing the class, and lack of application of the 3Rs. So it is necessary to develop an attitude of caring for the environment for students of the Social Studies Education Study Program. Alternatives that can be given to develop an attitude of environmental care can be through activities and integration of environment-based learning.